EXPLOITATION OF MINORS FOR PORNOGRAPHIC PURPOSES – THE SOCIODEMOGRAPHIC AND CRIMINAL PROFILE OF THE PERPETRATOR - Baic, Valentina Dj; Ivanovic, Zvonimir M; Oljaca, Milan V (NBP. Nauka, bezbednosti, policija, 2019)
The paper presents research in a form of a survey aimed at examining the sociodemographic and criminal profile of the perpetrator of the crime of displaying, acquiring and possession of pornographic material and exploitation of a juvenile for pornography under Article 185 of the Criminal Code of Serbia, with particular reference to the imposed criminal sanctions. The survey was conducted at the beginning of 2018 and included 62 convicted male persons aged 18 to 70, prosecuted under jurisdiction of the Special Prosecutor’s Office for Combating High-Tech Crime in the period from 2012 to 2016. The results of the research show that the perpetrators of the said criminal offense are exclusively male individuals of an average age of 36,6 years, whose structure in terms of the working status is extremely diverse, starting from workers of various occupations, students to pensioners. In terms of other socio-demographic characteristics, the results of the survey show that the largest percentage of the convicted offenders have completed secondary school, that the number of the employed and unemployed is the same, that they are not married, gravitate towards urban areas, and have not been convicted before. In terms of the modus operandi, the results of the survey show that two methods of execution are dominant: the first implies the use of P2P technology on the Internet and the use of certain closed networks, which allow searching, downloading and sharing of photos and audio-visual data whereas the other involves creating a false profile on the Facebook social network.